Disease and antimicrobial resistance surveillance for Nile tilapia pathogens in Lake Victoria, Kenya - Teplitz, E.M.; Mwainge, V.M.; Wacira, T.N.; Ogwai, C.; Mayianda, M.J.; Ochieng, Linnet; Patel, Ekta; Getchell, R.G.; Aura, C.M.; Fiorella, K.J. (Wiley, 2026)
The cage aquaculture industry in Lake Victoria, Kenya is growing explosively to meet increasing demand for fish, yet large-scale fish mortalities are prevalent and pose economic shocks with catastrophic livelihood impacts. To gain a more comprehensive understanding of fish health in Lake Victoria, our study applied: (1) survey of cage farmer accounts, perceptions and responses to fish kill events; (2) rapid-response investigation to a significant tilapia mortality event; (3) active disease surveillance; and (4) antimicrobial resistance (AMR) testing of bacterial pathogens via disk diffusion. There were 82 fish kills recalled from 2020 to 2023 with total mortalities exceeding 1.8 million tilapia; yet, only 39% of farmers reported to Kenyan institutions and 17% of farmers attempted medical treatment. Low dissolved oxygen (DO) levels and the isolation of Aeromonas jandaei, Enterobacter hormaechei and Staphylococcus epidermidis were implicated as suspected causes for a recent tilapia mortality event. Active disease surveillance detected trichodinids and monogeneans as common external parasites and identified an additional six bacterial species in tilapia (Acinetobacter soli, Bacillus cereus, Kocuria rhizophila, Micrococcus luteus, Plesiomonas shigelloides, Staphylococcus sciuri) previously published as fish pathogens. Furthermore, we identify AMR patterns that will support the development of host- and pathogen-specific thresholds.